Dynamics of African horse sickness virus nucleic acid and antibody in horses following immunization with a commercial polyvalent live attenuated vaccine. Issue 18 (25th April 2017) - Weyer, C.T.; Grewar, J.D.; Burger, P.; Joone, C.; Lourens, C.; MacLachlan, N.J.; Guthrie, A.J.
Highlights: Administration of AHS-LAV combinations can affect RNAemia level. Length of time between AHS-LAV combinations can affect RNAemia level. Use of AHS-LAV can complicate surveillance strategies. Multiple AHSV types contained in AHS-LAVs can increase risk of reassortment. Abstract: African horse sickness (AHS) is a fatal disease of equids relevant to the global equine industry. Detection of AHS virus (AHSV) during outbreaks has become more rapid and efficient with the advent of group specific reverse transcriptase quantitative polymerase chain reaction (GS RT-qPCR) assays to detect AHSV nucleic acid. Use of GS RT-qPCR together with recently described type specific (TS RT-qPCR) assays cannot only expedite diagnosis of AHS but also facilitate further evaluation of the dynamics of AHSV infection in the equine host. A potential limitation to the application of these assays is that they detect viral nucleic acid originating from any AHS live attenuated vaccine (LAV), which is the vaccine type routinely administered to horses in South Africa. The aim of this study was to contrast the dynamics and duration of the RNAaemia to the serological responses of horses following immunization with a commercial polyvalent AHSV-LAV using GS and TS RT-qPCR assays and serum neutralisation tests. The results of the study showed extended RNAemia in vaccinated horses, and that more horses tested positive on GS RT-qPCR with lower Cq values after receiving the AHSV-LAV containing types 1, 3 and 4 prior to the vaccine containing types 2, 6, 7 and 8, rather than when the vaccine combinations were reversed. Furthermore, lower Cq values were obtained when vaccines were administered 4 weeks apart as compared with a longer interval or 12 weeks apart. These findings are of particular relevance in regions where AHSV-LAVs are used as the use of these vaccines may complicate the accurate interpretation of diagnostic testing results.